The economic dimension of water use in wheat production to meet consumption needs and food security in Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2025)
Given the scarcity of water and the declining levels of non-renewable groundwater, this study aimed to determine the economic dimension of water use in wheat production to meet consumption needs and enhance food security in the Kingdom of Saudi Arabia during the period 1990–2023. The study revealed that, following the implementation of Resolution 335, the contribution of domestic production to meeting consumption needs ranged from a minimum of 5.92% to a maximum of 49.88% at a 95% confidence level. The strategic wheat reserve was estimated at approximately 3.61 million tons, with a food security index of 0.80 by the end of the 1990–2023 period. The contribution of production to achieving wheat food security ranged from 42.54% to 67.46%, while the contribution of imports ranged from 12.54% to 37.46%, also at a 95% confidence level. The amount of water used to achieve self-sufficiency and food security represents 83.3% and 5.68%, respectively, of the total water used in wheat production, which amounted to 84.54 billion cubic meters during the period 1990–2023. The study also showed that raising the wheat self-sufficiency rate to 50% would require cultivating an area equivalent to 40.55% of the total cultivated area of 893,370 hectares in 2023. Finally, the study recommends integrating local agricultural production with imports to ensure that the strategic wheat reserve does not exceed the current silo storage capacity, and that the self-sufficiency rate for wheat does not surpass 50%, so as to avoid a decline in both the value of plant production and the agricultural sector’s contribution to the gross domestic product.
Keywords: Water; Wheat; Self-sufficiency; Food Security; Strategic Stock